2017
DOI: 10.1111/ajco.12818
|View full text |Cite
|
Sign up to set email alerts
|

Lower trial participation by culturally and linguistically diverse (CALD) cancer patients is largely due to language barriers

Abstract: Aim: Clinical trials play a critical role in advancing cancer care, but international research shows that few cancer patients, particularly culturally and linguistically diverse (CALD) patients, participate in trials. This limits generalizability of trial results and increases health disparities. This study aimed to establish rates and correlates of trial participation among CALD patients in South Western Sydney Local Health District (SWSLHD), a highly culturally diverse area. Conclusions: Limited English prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…In addition, American studies have found significantly lower accrual of racially/ethnically diverse patients 6,7 . A similar trend is seen among Australia's culturally and linguistically diverse (CALD) people, 8 defined by the Australian Bureau of Statistics (ABS) as those born in countries other than “main English speaking countries.” 9,10…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In addition, American studies have found significantly lower accrual of racially/ethnically diverse patients 6,7 . A similar trend is seen among Australia's culturally and linguistically diverse (CALD) people, 8 defined by the Australian Bureau of Statistics (ABS) as those born in countries other than “main English speaking countries.” 9,10…”
Section: Introductionmentioning
confidence: 77%
“…Univariate and multivariable nominallogistic regression evaluated the association of knowledge and attitude scores with possible future trial participation, adjusting for Vietnamese/Anglo‐Australian background and past participation. Variables included were based on a previously published retrospective analysis of correlates of trial participation among CALD patients, revealing that language plays a significant role 8 ; and a study of CALD populations showing greater participation among previous trial participants 30 …”
Section: Methodsmentioning
confidence: 99%
“…Overall, this study by Smith et al 7 is important as it highlights that language remains as a major barrier that challenges us to search for innovative solutions. Similar difficulties have been reported previously especially in recruiting patients with South Asian background, and it has been suggested that senior doctors would approach those patients, as they would be seen as more trustworthy.…”
Section: Clinical Trials Culture and Language: More Than Meets The Eye?mentioning
confidence: 87%
“…In the current issue of this Journal, Smith et al 7 extracted 10 years of data from electronic health records of patients treated within the South Western Sydney region, and analyzed them retrospectively.…”
Section: Clinical Trials Culture and Language: More Than Meets The Eye?mentioning
confidence: 99%
“…However, this evidence was mainly based on people from Anglo‐Saxon cultures like the United Kingdom, Canada, and Australia and did not inform on the appropriateness of MBIs from other cultures. Although mindfulness originated from Eastern Buddhist philosophy, in psycho‐oncology research, people from culturally and linguistically diverse (CALD) groups are often excluded from studies involving MBIs . Consequently, their perspectives on mindfulness are not well understood.…”
Section: Introductionmentioning
confidence: 99%